Nurses’ experience with burnout and therole of perceived social support - Rizal Febri Yanto; Djudiyah Djudiyah; Nandy Agustin Syakarofath (University of Muhammadiyah Malang, 2022)
Nurses are among the health professionals at the forefront of dealing with patients identified as covid-19, particularly vulnerable to psychological fatigue. Various studies have found that perceived social support can assist nurses in dealing with difficult situations. The study's goal was to see how perceived social support affected nurses' burnout. A total of one hundred nurses took part in this study, which was conducted using random sampling techniques. The Multidimensional Scale of Perceived Social Support (MSSPS) and the Burnout Assessment Tool (BAT) are tools used to assess perceived social support and burnout, respectively. The results of the simple linear regression analysis revealed that perceived social support had an effect on nurse burnout in Balikpapan (adjustedR2 = 0.245; F(31,793) = 99, p = 0.001). The more social support nurses have, the less burnout they experience.